2008
DOI: 10.1126/science.1158545
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Regression in Cancer Patients by Very Low Doses of a T Cell–Engaging Antibody

Abstract: Previous attempts have shown the potential of T cells in immunotherapy of cancer. Here, we report on the clinical activity of a bispecific antibody construct called blinatumomab, which has the potential to engage all cytotoxic T cells in patients for lysis of cancer cells. Doses as low as 0.005 milligrams per square meter per day in non-Hodgkin's lymphoma patients led to an elimination of target cells in blood. Partial and complete tumor regressions were first observed at a dose level of 0.015 milligrams, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
758
1
10

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 939 publications
(785 citation statements)
references
References 26 publications
16
758
1
10
Order By: Relevance
“…Tumor doubling time in patients with ALL was assumed to be 33 days based on literature report, 20 and the derived k g was 0.00126 1/hr. The effect of T cell proliferation was not considered in the current simulation since it was reported that, on average, blinatumomab caused approximately a two-fold expansion of T cells in patients, 41 which would only lead to minor changes in τ. CD19 expression level on B cells was assigned at 20,000 receptors per cell based on literature report, 42 and this value was 2- to 5-fold lower than that of B cell lines used in vitro cytotoxicity assays (20,000 vs. 40,000 – 100,000 receptors per cell). 22,33,43–45 The blood and bone marrow blinatumomab concentration-response curves predicted by the TBE model are shown in Figure 5.…”
Section: Resultsmentioning
confidence: 99%
“…Tumor doubling time in patients with ALL was assumed to be 33 days based on literature report, 20 and the derived k g was 0.00126 1/hr. The effect of T cell proliferation was not considered in the current simulation since it was reported that, on average, blinatumomab caused approximately a two-fold expansion of T cells in patients, 41 which would only lead to minor changes in τ. CD19 expression level on B cells was assigned at 20,000 receptors per cell based on literature report, 42 and this value was 2- to 5-fold lower than that of B cell lines used in vitro cytotoxicity assays (20,000 vs. 40,000 – 100,000 receptors per cell). 22,33,43–45 The blood and bone marrow blinatumomab concentration-response curves predicted by the TBE model are shown in Figure 5.…”
Section: Resultsmentioning
confidence: 99%
“…The observed lymphocyte redistribution (and transient expression of T cell activation markers) was similar to what has been reported for the BiTE® antibody construct blinatumomab. 12 , 23 In contrast with blinatumomab, which targets CD19, recurrence of peripheral T cells during solitomab treatment was delayed or absent in most patients during the first 50 hours of treatment in the first patients enrolled, possibly indicating T-cell migration from the peripheral blood to the solid tumor; however, this hypothesis require further investigation. Prolonged therapy with dexamethasone was necessary in patients with impacted lymphocyte levels.…”
Section: Discussionmentioning
confidence: 99%
“…Proof of concept was shown early with blinatumomab in the setting of hematologic malignancies; 12 , 14 , 15 however, information on the applicability of BiTE® antibody constructs to the solid tumor setting remains very limited. 18 We report here the final results of the first-in-human phase 1 study of solitomab, a BiTE® antibody construct immunotherapy against EpCAM, in solid tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Continuous intravenous infusion (cIV) was tested in a subsequent phase 1 trial (MT103‐104), again among subjects with indolent NHL ( Figure 3, Table 2),54, 55 to mitigate toxicity and maintain exposures needed to sustain responses; it was hypothesized that intermittent dosing led to high C max and that the drug‐free period potentiated T‐cell cytokine release. The dose–exposure relationship was linear from 5–90 μg/m 2 /d, stable plasma blinatumomab levels were achieved rapidly with continuous infusion, and rapid clearance consistent with previous observations was observed 56.…”
Section: Clinical Experience With Blinatumomabmentioning
confidence: 99%